Tantangan dan Peluang Implementasi Perencanaan Pembangunan Partisipatif Desa-Desa di Indonesia - Olvit Olniwati Kayupa; Feliks Guampe; Join Hengkeng; Mikhael Jibrael Balo (Penerbit Goodwood, 2025)
Purpose: This study evaluates participatory development planning in Indonesian villages and identifies challenges and opportunities for improvement. Methodology: A literature review of 50 articles and reports was conducted, using content analysis to interpret findings. Results: The study identifies challenges such as low community involvement, elite dominance, ineffective communication, and unequal education access, while highlighting opportunities for improvement through capacity building, policy reform, innovative methods, and enhanced collaboration between village authorities, NGOs, and academic institutions. Conclusion: This study emphasizes the importance of community participation in village development planning as a foundation for achieving sustainable and inclusive development. Limitations: The study's reliance on existing literature may limit the depth of understanding of current practices. Contribution: The research provides insights to improve participatory development planning in Indonesian villages, guiding policymakers, researchers, and practitioners.